COMMUNICATIVE ENGLISH LEARNING MANAGEMENT WITH MULTIMEDIA READING INSTRUCTIONAL PACKAGE ON READING ABILITY AND VOCABULARY ACHIEVEMENT FOR THE PRIMARY SCHOOL STUDENTS (Practitioner Research, 2021)
Small schools usually have insufficient learning materials as well as a shortage of English teachers. Hence, students may not have enough opportunities to learn English. Therefore, this current study aimed to develop a multimedia reading instructional package that can enhance students’ interest and their eagerness to learn English for communication. The participants of this study consisted of 13 first graders from a primary school in Maha Sarakham, Northeastern Thailand by using a simple random sampling. The objectives of this study were: 1) to develop the learning management of English for communication which including a multimedia reading instructional  package, 2) to investigate the effectiveness of the English language learning management for communication by using the multimedia pronunciation activity package, and 3) to study the reading ability of the students who learned English for communication using a multimedia pronunciation activity package. The current study was conducted by using One Group Pretest-Posttest Design. The findings found that the effectiveness of the English language learning management plan for communication using the multimedia pronunciation activity package had an efficiency (E1 / E2) of 95.58 / 83.58 which was higher than the specified 80/80 criteria. The results also indicated that the students learning progress was increased by 0.70, or 70%. Moreover, it was revealed in the present study that the elementary school students who learned English for communication using a multimedia pronunciation activity package had an increased ability to read aloud.